Atomistic mechanisms of huntingtin N‐terminal fragment insertion on a phospholipid bilayer revealed by molecular dynamics simulations. Issue 7 (18th February 2014) - Côté, Sébastien; Wei, Guanghong; Mousseau, Normand
ABSTRACT The huntingtin protein is characterized by a segment of consecutive glutamines (QN) that is responsible for its fibrillation. As with other amyloid proteins, misfolding of huntingtin is related to Huntington's disease through pathways that can involve interactions with phospholipid membranes. Experimental results suggest that the N‐terminal 17‐amino‐acid sequence (httNT) positioned just before the QN region is important for the binding of huntingtin to membranes. Through all‐atom explicit solvent molecular dynamics simulations, we unveil the structure and dynamics of the httNTQN fragment on a phospholipid membrane at the atomic level. We observe that the insertion dynamics of this peptide can be described by four main steps—approach, reorganization, anchoring, and insertion—that are very diverse at the atomic level. On the membrane, the httNT peptide forms a stable α‐helix essentially parallel to the membrane with its nonpolar side‐chains—mainly Leu‐4, Leu‐7, Phe‐11 and Leu‐14—positioned in the hydrophobic core of the membrane. Salt‐bridges involving Glu‐5, Glu‐12, Lys‐6, and Lys‐15, as well as hydrogen bonds involving Thr‐3 and Ser‐13 with the phospholipids also stabilize the structure and orientation of the httNT peptide. These observations do not significantly change upon adding the QN region whose role is rather to provide, through its hydrogen bonds with the phospholipids' head group, a stable scaffold facilitating the partitioning of the httNT region in the membrane. Moreover, by staying accessible to the solvent, the amyloidogenic QN region could also play a key role for the oligomerization of httNTQN on phospholipid membranes. Proteins 2014; 82:1409–1427. © 2014 Wiley Periodicals, Inc.